Building Stronger Communities: Integrating Financial Resources for SME Empowerment - Noch, Muhammad Yamin; Rumasukun, Mohammad Ridwan (Manunggal Halim Jaya, 2024)
This literature review explores the integration of financial resources as a catalyst for empowering small and medium enterprises (SMEs) and fostering sustainable development. The study aims to examine key themes, methodologies, and findings from existing literature to elucidate the significance of diverse funding sources and collaborative partnerships in facilitating SME access to finance and promoting entrepreneurship. A comprehensive review of scholarly articles, theoretical frameworks, and empirical studies was conducted to synthesize insights into the integration of formal and informal financing options, their impact on SME empowerment, and implications for sustainable development. The findings highlight the importance of diversifying funding sources, optimizing capital structures, and fostering strategic partnerships among policymakers, practitioners, and stakeholders to create an enabling environment conducive to SME growth, resilience, and long-term sustainability. Key themes include the role of formal sources such as bank loans and venture capital, as well as informal sources including angel investors and community-based funds, in providing SMEs with access to capital for growth and innovation. Moreover, the study underscores the multifaceted contributions of SMEs to community development, social cohesion, and environmental stewardship, emphasizing the need for holistic approaches to SME empowerment that integrate economic, social, and environmental dimensions of sustainable development. The findings contribute to academic discourse and inform policymakers, practitioners, and business leaders about the importance of integrating financial resources for SME empowerment and advancing broader sustainable development goals.